2017
DOI: 10.4269/ajtmh.16-0496
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Trends in Fecal Biomarkers of Gut Function in Children from 1–24 Months in the MAL-ED Study

Abstract: Abstract. Growth and development shortfalls that are disproportionately prevalent in children living in poor environmental conditions are postulated to result, at least in part, from abnormal gut function. Using data from The Etiology, Risk Factors, and Interactions of Enteric Infections and Malnutrition and the Consequences for Child Health and Development (MAL-ED) longitudinal cohort study, we examine biomarkers of gut inflammation and permeability in relation to environmental exposures and feeding practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
103
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(115 citation statements)
references
References 33 publications
8
103
3
1
Order By: Relevance
“…The presence of ETEC in stool was associated with elevated faecal calprotectin concentrations. This is consistent with the recent literature demonstrating an association between enteric pathogens and elevated EE faecal markers [40]. In the MAL-ED study, a higher number of enteric pathogens in stool was associated with elevated concentrations of faecal myeloperoxidase and alpha-1antitrypsin in young children.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of ETEC in stool was associated with elevated faecal calprotectin concentrations. This is consistent with the recent literature demonstrating an association between enteric pathogens and elevated EE faecal markers [40]. In the MAL-ED study, a higher number of enteric pathogens in stool was associated with elevated concentrations of faecal myeloperoxidase and alpha-1antitrypsin in young children.…”
Section: Discussionsupporting
confidence: 92%
“…In the MAL-ED study, a higher number of enteric pathogens in stool was associated with elevated concentrations of faecal myeloperoxidase and alpha-1antitrypsin in young children. In addition, Campylobacter infections were associated with elevated faecal myeloperoxidase concentrations, and Giardia intestinalis infections were associated with elevated faecal neopterin concentrations [27,40,41]. In a later paper from this study, ETEC and Shigella were found to be positively associated with elevated myeloperoxidase concentrations [27].…”
Section: Discussionmentioning
confidence: 55%
“…Rice bran was shown to reduce AAT in neonatal pigs challenged with human Rotavirus infection 22 and is of translational importance herein as rice bran intake improved AAT levels in Nicaraguan infants ( Table 2 ). The lack of significant differences in levels of EED biomarkers for Mali may be due to the higher number of overall diarrheal episodes, the level of variability within individuals, and breastfeeding over time and across groups, yet these findings did concur with concentrations reported in the MAL-ED cohort 34 . EED biomarkers merit continuous review for relevance with growth outcomes due to extensive global variability in concentrations reported across studies 6,4951 .…”
Section: Discussionmentioning
confidence: 60%
“…Stool EED biomarkers, gut microbiome 32 and metabolome analysis 15, 33 became important surrogate markers for analysis as intestinal tissue from infants is not easily accessible to evaluate. Stool myeloperoxidase (MPO) 34 , calprotectin (CAL) 35 , and neopterin (NEO) 36 are indicators of inflammation; and alpha-1-antitrypsin (AAT) 34 is an indicator of barrier lumen disruption. Chronic, elevated concentrations of all four biomarkers have been associated with poor linear growth in infants up to 24 months old 10,3436 , and as the gut microbiome is maturing over the first 3 years of life 37, 38 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation